Structural and Functional Information of Human Hemoglobin Subunit μ - Han, Hui; Liu, Xichun; Wang, Yanfei; Yu, Lu; Gao, Shu‐Qin; Lin, Ying‐Wu (Chembiochem : a European journal of chemical biology, 2025)
The human hemoglobin subunit μ (Hb‐μ) has been identified as a potential biomarker for α‐thalassemia. However, little structural and functional information is available for this subunit. Here, we have overexpressed and purified a double mutant of C49S/C104S Hb‐μ and solved its X‐ray crystal structure. It adopts a typical protein fold of the globins, similar to that of the α‐subunit. The structure also reveals that the protein undergoes self‐oxidation of Met62 in the heme distal site, producing the form of sulfoxide (Met‐SO). The property and function have also been studied by spectroscopy, which shows that the protein has considerable peroxidase activity due to the presence of a catalytic His‐Arg pair in the heme distal site. The structure‐function relationship of Hb‐μ obtained in this study may provide useful insights into Hb‐related diseases. Hb subunit: The X‐ray crystal structure of the human subunit μ C49S/C104S mutant was determined, which adopts the typical protein fold of globins, whereas the distal Met62 is self‐oxidized to the sulfoxide form (Met‐SO).